2017
DOI: 10.1111/sifp.12029
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Health and Bodily Integrity in Tanzania

Abstract: Several policy initiatives support the empowerment of women to improve their reproductive health. Little is known, however, about the inverse effect that reproductive health might have on women's empowerment. Women are pressured to conform to their reproductive role, and an inability to do so might affect their empowerment, including control over their own body. Using a panel dataset of 504 married women in Northern Tanzania, we find that women who experienced a pregnancy loss show more tolerant views of partn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
1
0
0
Order By: Relevance
“…However, women’s sexual autonomy was found not to be a determinant of the number of children ever born after adjusted for all covariates. The finding is consistent with studies in other context where it was found no significant association between number of children ever born and sexual autonomy in Tanzania [ 110 ]; in Uganda [ 111 ] and in Cote d’Ivoire and Nigeria [ 112 ]. Furthermore, the findings also affirm the findings in South-West Nigeria [ 113 ] and Zambia [ 114 ].…”
Section: Discussionsupporting
confidence: 92%
“…However, women’s sexual autonomy was found not to be a determinant of the number of children ever born after adjusted for all covariates. The finding is consistent with studies in other context where it was found no significant association between number of children ever born and sexual autonomy in Tanzania [ 110 ]; in Uganda [ 111 ] and in Cote d’Ivoire and Nigeria [ 112 ]. Furthermore, the findings also affirm the findings in South-West Nigeria [ 113 ] and Zambia [ 114 ].…”
Section: Discussionsupporting
confidence: 92%